DESIGN, ANALYSIS AND RE-MODIFICATION OF CHAIN BLOCK SYSTEM (International Journal of Engineering Sciences & Management Research, 2017)
Chain block system plays an important role in an industry to carry the load/materials from one place to another. Computer aided design and analysis of chain block system is one of the techniques used in manufacturing sectors to arrive for the best manufacturing condition, which is an essential need for industry manufacturing of Chain block at lower cost. The objective of my paper work is to study the design of various components which are used in chain block system. A sufficient amount of research work has been described by researchers on the modification of chain hoist system. In a vision of above, my paper work present design, analysis and re-modification of chain block system.